Radiotherapy orchestrates natural killer cell dependent antitumor immune responses through CXCL8 - Walle, Thomas; Kraske, Joscha; Liao, Boyu; Lenoir, Bénédicte; Timke, Carmen; Halbach, Emilia von Bohlen Und; Tran, Florian; Griebel, Paul; Albrecht, Dorothee; Ahmed, Azaz; Suarez-Carmona, Meggy; Jimenez-Sanchez, Alejandro; et al. (Science advances, 2022)
Radiotherapy is a mainstay cancer therapy whose antitumor effects partially depend on T cell responses. However, the role of Natural Killer (NK) cells in radiotherapy remains unclear. Here, using a reverse translational approach, we show a central role of NK cells in the radiation-induced immune response involving a CXCL8/IL-8-dependent mechanism. In a randomized controlled pancreatic cancer trial, CXCL8 increased under radiotherapy, and NK cell positively correlated with prolonged overall survival. Accordingly, NK cells preferentially infiltrated irradiated pancreatic tumors and exhibited CD56(dim)-like cytotoxic transcriptomic states. In experimental models, NF-kappa B and mTOR orchestrated radiation-induced CXCL8 secretion from tumor cells with senescence features causing directional migration of CD56(dim) NK cells, thus linking senescence-associated CXCL8 release to innate immune surveillance of human tumors. Moreover, combined high-dose radiotherapy and adoptive NK cell transfer improved tumor control over monotherapies in xenografted mice, suggesting NK cells combined with radiotherapy as a rational cancer treatment strategy.
Gesehen am 24.01.2023